Exploration Of Central Kalimantan Peatland Fungi As Antibacterial Agents Against Antibiotic-Resistant Staphylococcus Aureus and Salmonella Typhimurium - Kusuma, Hari; Nawan; Alexandra, Francisca Dian (Barigas: Jurnal Riset Mahasiswa, 2025)
Pathogens such as Staphylococcus aureus and Salmonella typhimurium show increasing level of resistance to various antibiotics, thus encouraging efforts to find new antibacterial agents from natural sources, including peat soil fungi. This study aims to examine the characteristics and potential antibacterial activity of fungal isolates from peat soil in three different locations in Palangka Raya City, namely Kereng Bengkirai, Yos Sudarso Street, and the and the environmental area of Palangka Raya, University, against Staphylococcus aureus and Salmonella typhimurium bacteria. The research design used was a true experimental with a post-test only control group design model. Fungal isolates were obtained through inoculation and isolation from peat soil samples, then cultivated, extracted, and tested for antibacterial activity using the disk diffusion method. against two test bacteria. The results showed that fungal isolates from the third locations did not show growth inhibitory activity against Staphylococcus aureus or Salmonella typhimurium at the concentrations and testing method used. Fungal isolates from peat soil in Kereng Bengkirai Yos Sudarso street, and the Palangka Raya University area do not have antibacterial activity against Staphylococcus aureus and Salmonella typhimurium under the conditions and test methods applied Keywords: peat soil fungi, antibacterial, Staphylococcus aureus, Salmonella typhimurium, antibiotic resistance.